Does corporate taxation deter multinationals? Evidence from a historic event in Ireland - Holger Görg; Eric Strobl (Kiel Institute for the World Economy (IfW), 2014)
We use a unique exogenous corporate tax policy change in the Republic of Ireland to investigate how corporate taxation affects foreign direct investment at the extensive and intensive margin. To this end we construct exhaustive sectoral and plant level panel data and use difference-in-differences strategies. Our results do not provide strong evidence that the increase in corporate tax rates for exporters did affect the entry or exit of plants from the US or UK in Ireland. Entry rates of German firms seem to be negatively affected, however. At the intensive margin there is evidence that foreign plants in Ireland reduce the size of their operations in response to the tax change.
Keywords: F23; H25; 330; multinational companies; foreign direct investment; corporate tax; Ireland; difference-in-differences